Understanding in mathematics - Sierpinska, Anna (Studies in mathematics education series, 1994)
The concept of understanding in mathematics with regard to mathematics education is considered in this volume, the main problem for mathematics teachers being how to facilitate their students' understanding of the mathematics being taught.